6(z+6)=3(2z+12)=

Simple and best practice solution for 6(z+6)=3(2z+12)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(z+6)=3(2z+12)= equation:



6(z+6)=3(2z+12)=
We move all terms to the left:
6(z+6)-(3(2z+12))=0
We multiply parentheses
6z-(3(2z+12))+36=0
We calculate terms in parentheses: -(3(2z+12)), so:
3(2z+12)
We multiply parentheses
6z+36
Back to the equation:
-(6z+36)
We get rid of parentheses
6z-6z-36+36=0
We add all the numbers together, and all the variables
=0
z=0/1
z=0

See similar equations:

| 3x-6=53x6x | | 4(m+3)-2m=3m+1 | | (3•x)-4=-19 | | 9x-2x+64=9x+36 | | -2+3(k-4)=3k-2(1-3k) | | 6.1x=0.2(x+2) | | 4(0,5f-0,25)=6+f | | 6x+9+6x-3=4x+8x+3 | | 7(×+7)=49-x | | -4(-3x+3)=3x+4(3+3x) | | (0.98)^x=0.5 | | 5(m+3-4(m+2)=10 | | 4(f+3)-1=-(f-3) | | 1.5(4-w=-(1.5w-8) | | x+3+2x-3=-2(1-2x)-2(x+2) | | 3y-5+7y+10=8y-3 | | −11+10(p+10)=4−5(2p+11) | | 12x^2-72x+8000=0 | | |-8x+3|=4x | | x-23=17-3x | | 4*3x+5=-2 | | 5b^2-24b-20=0 | | -4-8=4(-3n=2) | | 10(5+w)=−3(w+5) | | 4y+8-6y=3 | | 4x+1/2=1/4 | | -4-8=4(-3n+2 | | 2x/9+1=5/6-4x | | 1/2z-4=10 | | -3n-2(n+3)=-4(n+1) | | 10.5=5x | | 6(z+6)=3(2z+12 |

Equations solver categories